Role of the Axonal Initial Segment in Psychiatric Disorders: Function, Dysfunction, and Intervention - Hsu, Wei-Chun Jim; Nilsson, Carol Lynn; Laezza, Fernanda (Frontiers in Psychiatry, 2014)
The progress of developing effective interventions against psychiatric disorders has been limited due to a lack of understanding of the mechanisms involved at a cellular and functional level underlying these disorders. Recent research findings focusing on exploring novel causes of psychiatric disorders have highlighted the importance of the axonal initial segment (AIS), a highly specialized neuronal structure critical for spike initiation of the action potential. In particular, the role of voltage-gated sodium channels and their interaction with other protein partners in a tightly-regulated macromolecular complex has been highlighted as a key component in the regulation of neuronal excitability, and deficits and excesses of excitability have been linked to the pathogenesis of brain disorders. Identification of the factors involved in the proper functioning of the AIS, as well as the regulatory pathways that impinge on this component can lead to the development of novel interventions that target the mechanistic causes of psychiatric disorders, increasing treatment efficacy while reducing off-target effects.